Competitive Routes for Electrochemical Oxidation of Substituted Diarylamines: the Guidelines. Issue 22 (21st September 2018) - Levitskiy, Oleg A.; Dulov, Dmitry A.; Nikitin, Oleg M.; Bogdanov, Alexey V.; Eremin, Dmitry B.; Paseshnichenko, Ksenia A.; Magdesieva, Tatiana V.
Abstract: Electrochemical oxidation of diphenylamines with electron‐donating and electron‐withdrawing substituents in various combinations was investigated. It was shown that the subsequent reaction channels for the radical cations are dependent on the location and electronic properties of the substituents in both phenyl rings. Guidelines for the prediction of the dominant reaction path were formulated. The conclusions developed will be useful for planning electrosynthesis. Digital simulation of the voltammograms allowed estimating the mechanism of N, N‐diaryl‐5, 10‐dihydrophenazine formation (which is one of the main reaction channels); the corresponding radical cations were isolated for the first time and characterized by X‐ray, electrochemical and spectral methods. Oxidation peak potentials for diarylaminyl anions (obtained using electrochemically generated base) were measured providing information for mechanistic estimation of anti/prooxidant activity of diarylamines in radical processes. Abstract : Electrochemical oxidation of diphenylamines with electron‐donating and electron‐withdrawing substituents in various combinations is investigated. Guidelines for prediction of the dominant reaction path are formulated based on the reaction mechanism.